If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13g + -96 = 6g + -75 Reorder the terms: -96 + 13g = 6g + -75 Reorder the terms: -96 + 13g = -75 + 6g Solving -96 + 13g = -75 + 6g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-6g' to each side of the equation. -96 + 13g + -6g = -75 + 6g + -6g Combine like terms: 13g + -6g = 7g -96 + 7g = -75 + 6g + -6g Combine like terms: 6g + -6g = 0 -96 + 7g = -75 + 0 -96 + 7g = -75 Add '96' to each side of the equation. -96 + 96 + 7g = -75 + 96 Combine like terms: -96 + 96 = 0 0 + 7g = -75 + 96 7g = -75 + 96 Combine like terms: -75 + 96 = 21 7g = 21 Divide each side by '7'. g = 3 Simplifying g = 3
| 0.2(25x-20)=5x+6 | | 13s+21=16s-12 | | X^3+6x^2+8x=480 | | 2b+5=180 | | 4s+80=8s-32 | | 0.2(15x+20)=3x+4 | | 8b-12=180 | | 9x-3=2(3x+4) | | 12y-54=3y+36 | | 8(2g)= | | 4x+6-x+9=3(x+5) | | 3+5x=-5 | | 15x^7-6x^4/3x^3 | | 12-2x+8+6x=2(2x-8) | | -3(7Y-1)+6Y=3(Y+4) | | 6(2x-3)=9x+12+3x | | -3/2y=-21 | | 4(5s+3)=-43 | | g/17-8=- | | (5x+4)=35 | | 7(3m-4)=63 | | 30+20h=150 | | (2w+9)+3(4w-1)-9w=4(3+2w)-3 | | 4x+6(1)=12 | | 2(3c+6)=24 | | 811-4/15 | | 2(6y-3)=60 | | 9(p-6)=25(p-1) | | 4x^5-5x^4-19x^3-7x^2+3x=0 | | 200x-x^2=20x+5600 | | 0.15x+0.50-0.10x=0.7 | | 60-20h=140 |